Jazz. Episode three, Our language [videorecording (DVD)] - Burns, Ken, 1953-; David, Keith; Marsalis, Wynton, 1961-; Sanders, John, 1925- (PBS Home Video ; Distributed by Paramount Home Entertainment, 2004)
By 1924 to 1928, jazz is everywhere in America and spreading abroad. For the first time, soloists and singers take center stage, transforming the music with their distinctive voices. This episode traces the careers of Louis Armstrong, Duke Ellington, Artie Shaw, Sidney Bechet, Bessie Smith, Earl Hines, Ethel Waters, Bix Beiderbecke, the first great white jazz artist and Benny Goodman, the son of Jewish immigrants.